Perancangan Sistem Informasi Keuangan PT. Shinta Furniture Berbasis Web - Maulina, Dian (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023DO - 10.24843/JLK.2023.v12.i02.p28, 2023)
Shinta Furniture is a factory engaged in the furniture and fertilizer sector. The role of the computer as a sophisticated tool will not reach its maximum level if it has not been designed with a system that can double as a data processing process. However, the financial information system at PT Shinta Furniture still uses a desktop system. The existing financial system cannot be transferred to another computer. This study aims to facilitate access to financial staff. With this the researchers created and developed a new financial system at PT. Shinta Furniture based on WEB. This financial system uses a descriptive research method with the type of case study research in companies where the data collection techniques used include interviews, observational literature studies for data analysis techniques using the waterfall. The initial stage of this design is to collect research data regarding the website to be designed. In designing the system the author uses Context Diagrams and DFD (Data Flow Diagrams). For database design the authors use conceptual databases, logical databases and physical databases. The main components in designing this system use the MySQL database. The research result is a WEB-based financial information system so that it can be used to facilitate access. This system displays incoming and outgoing money data. On this website there is a report printing feature that can be printed according to the desired month and year.